Stream periphyton response to phosphorus loading events is constrained by antecedent conditions - Schneider, Natalie (University of Waterloo, 2025)
Phosphorus (P) loadings to streams often occur in short duration events associated with runoff from human activities. Although it has been shown that stream periphyton can uptake and assimilate event-based P, the role of antecedent P concentrations in modulating P uptake from event-based loadings and resulting effects on periphyton structure and function is not known. To assess effects of antecedent P concentration on stream periphyton response to short-term P loading events, we completed two 26-day artificial stream experiments at the Thames River Experimental Stream Sciences (TRESS) Centre in London, Canada. Experiments consisted of exposing periphyton communities in nine artificial streams to a range of 48-hour P loading event concentrations (15 to 690 μg P/L) under low (10 μg P/L) or high (50 μg P/L) antecedent P concentrations. Periphyton was sampled one day before, one day after and 10 days after P loading events to quantify periphyton structure (ash free dry mass (AFDM), chlorophyll a (chl a), P content) and function (P uptake, benthic metabolism, cellulose decomposition, biomass growth, chl a accumulation). Under low antecedent P conditions one day after the P event, P content and P uptake had a positive linear relationship with event concentration and this was similarly seen in biomass and chl a ten days after the P event. One day after the P event in high antecedent streams, P content and P uptake showed a positive linear response with P event concentration, but this additional P in periphyton did not lead to increases in biomass and chl a. Whereas, a negative linear relationship with event concentration and P uptake was seen ten days after the P event. Measures of periphyton function (benthic metabolism and cellulose decomposition) were unaffected by P event size and regardless of the antecedent condition. These findings suggest that high antecedent P concentrations caused cellular saturation of periphyton limiting the assimilation of P from event-based P loads. Therefore, streams with high antecedent P may deliver reduced water purification benefits with regards to attenuating P transport to downstream ecosystems at risk of eutrophication. Management actions to reduce antecedent P concentrations will be needed to rehabilitate ecosystem service provision in streams chronically enriched in P.
Keywords: periphyton; phosphorus; eutrophication; nutrient loading